Effect of Spirulina platensis Supplementation on Nutritional and Biochemical Parameters of Under Five Years Malnourished Children from an Orphanage in Douala, Cameroon - Kana Sop Marie Modestine; Namadi Muhamadu; Tetanye Ekoe; Gouado Inocent (Journal of Pharmacy and Nutrition Sciences, 2015)
Malnutrition is the underlying cause of 50% of morbidity and mortality in the under-five age group. Its frequencies have been increasing in young Cameroon children during the past three decades (stunting ≥ 38%; anemia ≥ 58%; Zinc ≥ 69% and vitamin A ≥ 38%) We carried out a prospective study to assess the supplementation effect of Spirulina platensis on moderate and mild malnutrition on children under five years old. Seven children (4-5 years) were enrolled in this study. Children were enrolled in nutritional rehabilitation for 25 days. Each child received 8g of supplement daily, 4g in the morning and 4g in the evening. Anthropometric and haematologic parameters were measured before and after rehabilitation. Mild and moderate malnutrition, wasting and underweight was seen in 4 children anthropometrically (no child was stunted) and haematologically in all 7 children before rehabilitation started. The children were weighted four times (First week at enrollment (W1), week 2 (W2), Week 3 (W3), Week 4 (W4)). After 25 days, a significant gain in weight was observed and varying from 17.21 ± 2.00Kg (W1) to 18.45 ± 2.07Kg (W2) and from 18.143 ± 1.77Kg (W3) to 18.67 ± 1.93Kg (W4) with their respective P- values at 0.02 (W2), 0.02 (W3) and 0.04 (W4) after rehabilitation. The following biomarkers and their constants also showed a significant variation: calcium (73.91 ± 16.89mg/L vs 88.41 ± 14.83mg/L (p = 0.03), mean cell volume (86.14 ± 4.38 fl vs 83.86 ± 4.83 fl (p = 0.04) and mean cell haemoglobin concentration (32.10 ± 0.38 g/dL vs 34.27 ± 3.35 g/dL (p = 0.03) respectively before and after rehabilitation. Other biomarkers (proteins, haemoglobin, haematocrit, platelets, red blood cells, white blood cells, neutrophiles, eosinophiles, basophiles, monocytes, lymphocytes) had also increased in non a significant manner. The study showed that spirulina platensis impact positively in the fight against malnutrition by improving weight and raising the blood content of biomarkers due to its high content of proteins (60-70%) and pigments.